Effect of Intracerebroventricular MOTS-c Infusion on Peripheral Uncoupling Proteins in Rats - Bahar, Mehmet Refik; Tekin, Suat; Beytur, Asiye; Onalan, Ebru Etem; Colak, Cemil; Sandal, Suleyman (Karger, 2021)
[Abstract Not Available]
Keywords: MOTS-c; UCP1; UCP3; BAT; WAT